2022
DOI: 10.7759/cureus.31603
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Nursing Practice Environment and Innovative Behavior in the Al-Madinah Region, Saudi Arabia: A Descriptive Study

Abstract: Background and objectiveA positive and supportive practice environment is essential for inspiring innovation in nursing. Innovative behaviors (IBs) could motivate nurses to devise solutions in several domains, such as identifying and solving workplace problems, building new work methods, delivering their services efficiently and effectively, adopting new medical technology advancements, and leading the change process to face current challenges in healthcare. In this study, we aimed to investigate the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…This result was matched with a research conducted in Egypt by [ 28 ] who reported that innovation output recorded the highest agreement of staff nurses about innovative behavior domains. Also, with [ 29 ] who conducted their study in Saudi Arabia and found that Idea search domain had the highest score.…”
Section: Discussionmentioning
confidence: 98%
“…This result was matched with a research conducted in Egypt by [ 28 ] who reported that innovation output recorded the highest agreement of staff nurses about innovative behavior domains. Also, with [ 29 ] who conducted their study in Saudi Arabia and found that Idea search domain had the highest score.…”
Section: Discussionmentioning
confidence: 98%
“…In nursing management, there are three functional roles: operational nurse manager (performs duties at the unit level), intermediate nurse manager (performs duties at the department level), and top-level nurse manager (performs his or her function at the organizational level) [ 8 ]. Top-level managers continue to make the vast majority of healthcare decisions in Saudi Arabia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%